(untitled) - HOLZNER, STEVEN (USA, 1993)
1.C++ Primer: Code and Classes / 2.Building a Program with the MFC Library / 3.The MFC Document and View Classes / 4.Using the CMenu Class / 5.Using the CDialogs Class: Dialog Boxes I / 6.Using the CDialogs Class: Dialog Boxes II / 7.The Predefined MFC Dialog Boxes / 8.MFC Drawing Functions and a Paint Program / 9.MFC File Handling / 10.Multiple MFC Documents / 11.Multiple MFC Views / 12.Exception Handling and Diagnostics / 13.Object Linking and Embedding / 14.Using VBX Controls / 15.Windows Program Desing
Incluye índice pag.721
Keywords: PROGRAMAS PARA COMPUTADOR